2020
DOI: 10.1002/adma.202005763
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Deposition of Lithium Particles Enabled by Ultraconformal and Stretchable Graphene Film for Lithium Metal Batteries

Abstract: Originating from inhomogeneous Li deposition and dissolution, the formation of dendritic and/or dead Li lies as a fundamental barrier to the practical implementation of Li metal anodes for high‐energy Li‐ion batteries. Here, an ultraconformal and stretchable solid‐electrolyte interphase (SEI) composed of parallelly stacked few‐layer defect‐free graphene nanosheets, which can deform to remain ultraconformal during the expansion and shrinkage of micro‐sized Li metal particles is reported. The shape‐adaptive grap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(48 citation statements)
references
References 56 publications
2
46
0
Order By: Relevance
“…[14] All the abovementioned limitations can be overcome or reduced if dendrite growth/breakage can be prevented during the deposition/ dissolution process. Many studies have been reported on the construction of dendrite-free metal anodes: a) fabrication of modified electrodes or metal substrate surfaces, [15][16][17][18][19][20][21][22][23][24] b) synthesis of new electrolytes, [25][26][27][28][29] c) use of solid electrolytes, [22,[30][31][32] and d) improvement of the electrode-electrolyte interface. [9,15,33,34] However, these studies have rarely focused on the properties, such as the stability of dendrites during charging and discharging, of dendrites.…”
mentioning
confidence: 99%
“…[14] All the abovementioned limitations can be overcome or reduced if dendrite growth/breakage can be prevented during the deposition/ dissolution process. Many studies have been reported on the construction of dendrite-free metal anodes: a) fabrication of modified electrodes or metal substrate surfaces, [15][16][17][18][19][20][21][22][23][24] b) synthesis of new electrolytes, [25][26][27][28][29] c) use of solid electrolytes, [22,[30][31][32] and d) improvement of the electrode-electrolyte interface. [9,15,33,34] However, these studies have rarely focused on the properties, such as the stability of dendrites during charging and discharging, of dendrites.…”
mentioning
confidence: 99%
“…Similarly, stacked graphene layers were reported to protect Li metal anode by a facile and low-cost strategy (Figure 16e). [280] The graphene was from mechanical shear-induced exfoliation of graphite, and then incorporated into Li foil by parallel alignment. The dense graphene layers not only acted as ultra-conformal SEI layer on Li anode, but also functioned as a shape-adaptive protective skin for Li deposition beneath it.…”
Section: Creating Protective Layers On LI Metalmentioning
confidence: 99%
“…e) Schematic illustration of Li deposition behavior with nondeformable SEI and deformable SEI with graphene coating. Reproduced with permission [280]. Copyright 2019, Wiley-VCH.…”
mentioning
confidence: 99%
“…To date, various methods aiming to engineer the electrode—electrolyte interface have been shown to be effective in optimizing the SEI layer and suppressing lithium dendrite growth. Strategies include optimizing electrolyte composition, [ 151 ] using additives, [ 152 ] constructing an artificial SEI, [ 153,154 ] use of graphene, [ 155 , 156 ] or covalent organic framework protection layers, [ 157 ] and lowering anode roughness and stress. [ 158,159 ]…”
Section: Ec‐afm For the Understanding Of Libs And Their Materialsmentioning
confidence: 99%